Glymphatic Dysfunction: A Bridge Between Sleep Disturbance and Mood Disorders - Yan, Tao; Qiu, Yuefeng; Yu, Xinfeng; Yang, Linglin (Frontiers in Psychiatry, 2021)
Mounting evidence demonstrates a close relationship between sleep disturbance and mood disorders, including major depression (MDD) and bipolar disorder (BD). According to the classical two-process model of sleep regulation, circadian rhythms driven by the light-dark cycle and sleep homeostasis modulated by the sleep-wake cycle are disrupted in mood disorders. However, the exact mechanism of interaction between sleep and mood disorders remains unclear. Recent discoveries of the glymphatic system and its dynamic fluctuation with sleep provide a plausible explanation. The diurnal variation of the glymphatic circulation is dependent on the astrocytic activity and polarization of water channel protein aquaporin-4 (AQP4). Both animal and human studies have reported suppressed glymphatic transport, abnormal astrocytes, and depolarized AQP4 in mood disorders. In this study, the “glymphatic dysfunction” hypothesis which suggests that the dysfunctional glymphatic pathway serves as a bridge between sleep disturbance and mood disorders is proposed.